Guia prático de procedimentos técnicos para avaliação de cursos de graduação no Centro de Informática da UFPB, a partir do SINAES - Cavalcanti, Lourdes Maria Rodrigues (2019)
This dissertation had as general objective to elaborate a practical theoretical manual of standardized technical procedures that determined the actions to be adopted, on the occasion of the next evaluations of the undergraduate courses offered by the Center of Informatics of the UFPB, from the Instrument of Evaluation of Graduation Courses - Face and Distance - of SINAES. The present research, regarding the approach, was of the qualitative type, with historical procedure, being, as far as the nature, an applied research; in relation to the objectives, was a descriptive research and used as a procedure the bibliographic research with documentary strategy. The research structure was built based on SINAES. Historically, the regulations of higher education in Brazil have been contextualized since 1983; the components, instruments, objectives and evolution of SINAES, from 2004 to 2018, the New Instruments of 2017 were analyzed and the aim was to build the state of the art of the evaluation of higher education, with a focus on SINAES, consulting in the month of February 2019, the dissertations and theses available in the Bank of Theses of CAPES, whose search term was the acronym SINAES. Our theoretical foundation on the Evaluation of Higher Education in Brazil was based on - in addition to the specific legislation - the Authors Dilvo Ilvo Ristoff, José Dias Sobrinho, Claudia Maffini Griboski and Robert Verhine. The results of the present study were based on the elaboration of a Practical Theory Manual, based on the SWOT analysis, complemented by the PDCA tool for the IC / UFPB undergraduate courses, based on the External Evaluation Reports in loco. The present study concluded that the application of the SWOT analysis, as an institutional management tool, elaborated from the PDI and the Reports of the on-site Evaluations, of any graduation course, complemented by the PDCA tool, is timely, viable and feasible, being fundamental for the generation of strategies directed to the adaptation to the precepts established by the SINAES, focusing on strengthening the quality of the evaluated courses.